Detection of heterozygotes for homocystinuria: Study of sulphur-containing amino acids in plasma and urine after L-methionine loading. Issue 7 (July 1974) - Sardharwalla, I. B.; Fowler, B.; Robins, A. J.; Komrower, G. M.
Abstract : Twelve parents of patients with homocystinuria and 12 normal control subjects were given standard L-methionine loads. Determination of plasma concentrations of homocystine and cysteine-homocysteine disulphide, of urine concentration ratios of homocystine: cystine, cysteine-homocysteine disulphide: cystine, and homocysteic acid: cysteic acid allowed a distinction to be made between the two groups. The findings indicate the value of the L-methionine loading test for detection of heterozygotes for homocystinuria, particularly where facilities for fibroblast culture and cystathionine synthase assay are not available.